The effect of financial inclusion on unemployment reduction - evidence from non-oil producing Arab countries. (19th July 2021) - Alshyab, Nooh; Sandri, Serena; Daradkah, Demeh
The non-oil producing Arab countries of the Middle East and North Africa are suffering from chronic high unemployment rates, especially among the youth. The availability of affordable and secure financial services is considered as one of the pillars for generating economic growth, stimulating job creation and reducing unemployment. This study investigates the link between financial inclusion and unemployment in non-oil exporting Arab countries. This is done via estimating an index for financial inclusion from 2008 to 2018 for Egypt, Jordan, Lebanon, Morocco, and Tunisia based on the methodology developed by Sarma. The estimated index reveals an overall average-to-low level of financial inclusion. The effect of financial inclusion on unemployment is then tested based on a modified version of Okun's law. The results of a random effect model reveal a significant negative effect both of financial inclusion and of real output growth on unemployment.